Nahal Yarmuth 38: a new and unique Pre-Pottery Neolithic B site in central Israel. (October 2019) - Gopher, Avi; Eirikh-Rose, Anna; Ashkenazi, Hai; Marco, Eyal; May, Hila; Makoviychuk, Yulia; Sapir-Hen, Lidar; Galmor, Shirad; Schechter, Heeli C.; Ackerfeld, Dana; Haklay, Gil; Zutovski, Katia
Abstract: Abstract : The small, Middle Pre-Pottery Neolithic B site (tenth millennium cal BP) of Nahal Yarmuth 38 in central Israel consists of a unique series of rectilinear structures with plastered floors, beneath which multiple interments were found. The nature of the finds combined with existing knowledge of burial customs of this period make Nahal Yarmuth 38 an ideal site for investigating designated burial sites in the Middle Pre-Pottery Neolithic B.